Generating Anti-TIGIT and CD155 Monoclonal Antibodies for Tumor Immunotherapy - Yu-Hang Duan; Yan-lin Bian; Jian-Wei Zhu (Georg Thieme Verlag KG, 2022)
Many studies have confirmed that the human poliovirus receptor (PVR; CD155) is related to tumor cell migration, invasion, and thus tumor progression. A PVR receptor binds its ligand T cell Ig and the ITIM domain (TIGIT) to inhibit the function of T and NK cells, thereby allowing tumors to evade immune surveillance. In this study, two IgG1 monoclonal antibodies, anti-CD155 and anti-TIGIT, were expressed by the mammalian transient transfection system, then, antibody-dependent cell-mediated cytotoxicity, antibody-binding affinity, and antitumor efficacy were evaluated subsequently in vitro. In this work, protein A affinity chromatography was used for antibodies' purification. Analysis methods included Western blot, enzyme-linked immunosorbent assay, and flow cytometry. Our data suggested that both the two monoclonal antibodies have a purity of higher than 90%, and bound tightly to the antigen with dissociation constant (K d) and 50% effective concentrations (EC50) below micromolar range. Most notably, these antibodies promote antitumor activity of immune cells in vitro. Therefore, our study laid down the foundation for subsequent in vivo experiments for further evaluation.